5 - Identification, Collection and Domestication of Medicinal Plants in Southeastern Nigeria: DOI: 10.4314/ad.v30i3.22230 - Nwufo, Martin I.; Ibe, Α. Ε. (Africa Development, 2005)
Field studies were conducted to investigate the medicinal plants, through identification, collection and domestication of these plants in southeastern, Nigeria. Questionnaire, personal interview and review of available records shows that out of forty-three plants about fifteen were undergoing domestication in the course of this research. This study revealed that much has not been done to domesticate these medicinal plants in Southeastern Nigeria. It was equally discovered that the medicinal plants have other uses as some could be used as vegetables, fruits, trees, ornamentals etc. From the results of this study, it is believed that nature has everything we need to exist happily on earth. But our inability to positively exploit nature makes the difference. If the result and recommendations of this study are strictly implemented, we hope for a better future.